مقالات

القسم 7.7 الإجابات - الرياضيات


1. (y_ {1} = 2x ^ {3} sum_ {n = 0} ^ { infty} frac {(- 4) ^ {n}} {n! (n + 2)!} x ^ {n}؛ quad y_ {2} = x + 4x ^ {2} -8 left (y_ {1} ln x-4 sum_ {n = 1} ^ { infty} frac {(- 4 ) ^ {n}} {n! (n + 2)!} left ( sum_ {j = 1} ^ {n} frac {j + 1} {j (j + 2)} right) x ^ {n} يمين) )

2. (y_ {1} = x sum_ {n = 0} ^ { infty} frac {(- 1) ^ {n}} {n! (n + 1)!} x ^ {n}؛ quad y_ {2} = 1-y_ {1} ln x + x sum_ {n = 1} ^ { infty} frac {(- 1) ^ {n}} {n! (n + 1) !} left ( sum_ {j = 1} ^ {n} frac {2j + 1} {j (j + 1)} right) x ^ {n} )

3. (y_ {1} = x ^ {1/2}؛ quad y_ {2} = x ^ {- 1/2} + y_ {1} ln x + x ^ {1/2} sum_ {n = 1} ^ { infty} frac {(- 1) ^ {n}} {n} x ^ {n} )

4. (y_ {1} = x sum_ {n = 0} ^ { infty} frac {(- 1) ^ {n}} {n!} x ^ {n} = xe ^ {- x} ؛ quad y_ {2} = 1-y_ {1} ln x + x sum_ {n = 1} ^ { infty} frac {(- 1) ^ {n}} {n!} left ( sum {j = 1} ^ {n} frac {1} {j} right) x ^ {n} )

5. (y_ {1} = x ^ {1/2} sum_ {n = 0} ^ { infty} left (- frac {3} {4} right) ^ {n} frac { prod_ {j = 1} ^ {n} (2j + 1)} {n!} x ^ {n}؛ quad y_ {2} = x ^ {- 1/2} - frac {3} {4 } يسار (y_ {1} ln xx ^ {1/2} sum_ {n = 1} ^ { infty} left (- frac {3} {4} right) ^ {n} frac { prod_ {j = 1} ^ {n} (2j + 1)} {n!} left ( sum_ {j = 1} ^ {n} frac {1} {j (2j + 1)} يمين) x ^ {n} right) )

6. (y_ {1} = x sum_ {n = 0} ^ { infty} frac {(- 1) ^ {n}} {n!} x ^ {n} = xe ^ {- x} ؛ quad y_ {2} = x ^ {- 2} left (1+ frac {1} {2} x + frac {1} {2} x ^ {2} right) - frac {1} {2} left (y_ {1} ln xx sum_ {n = 1} ^ { infty} frac {(- 1) ^ {n}} {n!} left ( sum_ {j = 1 } ^ {n} frac {1} {j} right) x ^ {n} right) )

7. (y_ {1} = 6x ^ {3/2} sum_ {n = 0} ^ { infty} frac {(- 1) ^ {n}} {4 ^ {n} n! (n +3)!} x ^ {n}؛ quad y_ {2} = x ^ {- 3/2} left (1+ frac {1} {8} x + frac {1} {64} x ^ {2} right) - frac {1} {768} left (y_ {1} ln x-6x ^ {3/2} sum_ {n = 1} ^ { infty} frac {(- 1) ^ {n}} {4 ^ {n} n! (n + 3)!} left ( sum_ {j = 1} ^ {n} frac {2j + 3} {j (j + 3) } يمين) × ^ {n} يمين) )

8. (y_ {1} = frac {120} {x ^ {2}} sum_ {n = 0} ^ { infty} frac {(- 1) ^ {n}} {n! (n +5)!} x ^ {n}؛ quad y_ {2} = x ^ {- 7} left (1+ frac {1} {4} x + frac {1} {24} x ^ {2 } + frac {1} {144} x ^ {3} + frac {1} {576} x ^ {4} right) - frac {1} {2880} left (y_ {1} ln x- frac {120} {x ^ {2}} sum_ {n = 1} ^ { infty} frac {(- 1) ^ {n}} {n! (n + f)!} يسار ( sum_ {j = 1} ^ {n} frac {2j + 5} {j (j + 5)} right) x ^ {n} right) )

9. (y_ {1} = frac {x ^ {1/2}} {6} sum_ {n = 0} ^ { infty} (- 1) ^ {n} (n + 1) (n +2) (n + 3) x ^ {n}؛ quad y_ {2} = x ^ {- 5/2} left (1+ frac {1} {2} x + x ^ {2} يمين) -3y_ {1} ln x + frac {3} {2} x ^ {1/2} sum_ {n = 1} ^ { infty} (- 1) ^ {n} (n + 1) (n + 2) (n + 3) left ( sum_ {j = 1} ^ {n} frac {1} {j (j + 3)} right) x ^ {n} )

10. (y_ {1} = x ^ {4} left (1 - frac {2} {5} x right)؛ quad y_ {2} = 1 + 10x + 50x ^ {2} + 200x ^ {3} - 300 left (y_ {1} ln x + frac {27} {25} x ^ {5} - frac {1} {30} x ^ {6} right) )

11. (y_ {1} = x ^ {3}؛ quad y_ {2} = x ^ {- 3} left (1- frac {6} {5} x + frac {3} {4} x ^ {2} - frac {1} {3} x ^ {3} + frac {1} {8} x ^ {4} - frac {1} {20} x ^ {5} right) - frac {1} {120} يسار (y_ {1} ln x + x ^ {3} sum_ {n = 1} ^ { infty} frac {(- 1) ^ {n} 6! } {n (n + 6)!} x ^ {n} right) )

12. (y_ {1} = x ^ {2} sum_ {n = 0} ^ { infty} frac {1} {n!} left ( prod_ {j = 1} ^ {n} frac {2j + 3} {j + 4} right) x ^ {n}؛ quad y_ {2} = x ^ {- 2} left (1 + x + frac {1} {4} x ^ { 2} - frac {1} {12} x ^ {3} right) - frac {1} {16} y_ {1} ln x + frac {x ^ {2}} {8} sum_ { n = 1} ^ { infty} frac {1} {n!} left ( prod_ {j = 1} ^ {n} frac {2j + 3} {j + 4} right) left ( sum_ {j = 1} ^ {n} frac {(j ^ {2} + 3j + 6)} {j (j + 4) (2j + 3)} right) x ^ {n} )

13. (y_ {1} = x ^ {5} sum_ {n = 0} ^ { infty} (- 1) ^ {n} (n + 1) (n + 2) x ^ {n}؛ quad y_ {2} = 1- frac {x} {2} + frac {x ^ {2}} {6} )

14. (y_ {1} = frac {1} {x} sum_ {n = 0} ^ { infty} frac {(- 1) ^ {n}} {n!} left ( prod_ {j = 1} ^ {n} frac {(j + 3) (2j-3)} {j + 6} right) x ^ {n}؛ quad y_ {2} = x ^ {- 7} left (1+ frac {26} {5} x + frac {143} {20} x ^ {2} right) )

15. (y_ {1} = x ^ {7/2} sum_ {n = 0} ^ { infty} frac {(- 1) ^ {n}} {2 ^ {n} (n + 4 )!} x ^ {n}؛ quad y_ {2} = x ^ {- 1/2} left (1- frac {1} {2} x + frac {1} {8} x ^ {2 } - frac {1} {48} x ^ {3} right) )

16. (y_ {1} = x ^ {10/3} sum_ {n = 0} ^ { infty} frac {(- 1) ^ {n} (n + 1)} {9 ^ {n }} left ( prod_ {j = 1} ^ {n} frac {3j + ​​7} {j + 4} right) x ^ {n}؛ quad y_ {2} = x ^ {- 2 / 3} left (1+ frac {4} {27} x- frac {1} {243} x ^ {2} right) )

17. (y_ {1} = x ^ {3} sum_ {n = 0} ^ {7} (- 1) ^ {n} (n + 1) left ( prod_ {j = 1} ^ { n} frac {j-8} {j + 6} right) x ^ {n}؛ quad y_ {2} = x ^ {- 3} left (1+ frac {52} {5} x + frac {234} {5} x ^ {2} + frac {572} {5} x ^ {3} + 143x ^ {4} right) )

18. (y_ {1} = x ^ {3} sum_ {n = 0} ^ { infty} frac {(- 1) ^ {n}} {n!} left ( prod_ {j = 1} ^ {n} frac {(j + 3) ^ {2}} {j + 5} right) x ^ {n}؛ quad y_ {2} = x ^ {- 2} left (1 + frac {1} {4} x right) )

19. (y_ {1} = x ^ {6} sum_ {n = 0} ^ {4} (- 1) ^ {n} 2 ^ {n} left ( prod_ {j = 1} ^ { n} frac {j-5} {j + 5} right) x ^ {n}؛ quad y_ {2} = x (1 + 18x + 144x ^ {2} + 672x ^ {3} + 2016x ^ {4}) )

20. (y_ {1} = x ^ {6} left (1+ frac {2} {3} x + frac {1} {7} x ^ {2} right)؛ quad y_ {2 } = x left (1+ frac {21} {4} x + frac {21} {2} x ^ {2} + frac {35} {4} x ^ {3} right) )

21. (y_ {1} = x ^ {7/2} sum_ {n = 0} ^ { infty} (- 1) ^ {n} (n + 1) x ^ {n}؛ quad y_ {2} = x ^ {- 7/2} left (1- frac {5} {6} x + frac {2} {3} x ^ {2} - frac {1} {2} x ^ {3} + frac {1} {3} x ^ {4} - frac {1} {6} x ^ {5} right) )

22. (y_ {1} = frac {x ^ {10}} {6} sum_ {n = 0} ^ { infty} (- 1) ^ {n} 2 ^ {n} (n + 1 ) (n + 2) (n + 3) x ^ {n}؛ quad y_ {2} = left (1- frac {4} {3} x + frac {5} {3} x ^ {2 } - frac {40} {21} x ^ {3} + frac {40} {21} x ^ {4} - frac {32} {21} x ^ {5} + frac {16} { 21} × ^ {6} right) )

23. (y_ {1} = x ^ {6} sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m} prod_ {j = 1} ^ {m} (2j +5)} {2 ^ {m} m!} x ^ {2m}؛ quad y_ {2} = x ^ {2} left (1+ frac {3} {2} x ^ {2} يمين) - frac {15} {2} y_ {1} ln x + frac {75} {2} x ^ {6} sum_ {m = 1} ^ { infty} frac {(- 1) ^ {m} prod_ {j = 1} ^ {m} (2j + 5)} {2 ^ {m + 1} m!} left ( sum_ {j = 1} ^ {m} frac {1 } {j (2j + 5)} right) x ^ {2m} )

24. (y_ {1} = x ^ {6} sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m}} {2 ^ {m} m!} x ^ { 2m} = x ^ {6} e ^ {- x ^ {2}}؛ quad y_ {2} = x ^ {2} left (1+ frac {1} {2} x ^ {2} يمين) - frac {1} {2} y_ {1} ln x + frac {x ^ {6}} {4} sum_ {m = 1} ^ { infty} frac {(- 1) ^ {m}} {2 ^ {m} m!} left ( sum_ {j = 1} ^ {m} frac {1} {j} right) x ^ {2m} )

25. (y_ {1} = 6x ^ {6} sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m}} {4 ^ {m} m! (m + 3 )!} x ^ {2m}؛ quad y_ {2} = 1 + frac {1} {8} x ^ {2} + frac {1} {64} x ^ {4} - frac {1 } {384} left (y_ {1} ln x-3x ^ {6} sum_ {m = 1} ^ { infty} frac {(- 1 (^ {m}} {4 ^ {m} m! (m + 3)!} left ( sum_ {j = 1} ^ {m} frac {2j + 3} {j (j + 3)} right) x ^ {2m} right) )

26. (y_ {1} = frac {x} {2} sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m} (m + 2)} {m!} x ^ {2m}؛ quad y_ {2} = x ^ {- 1} -4y_ {1} ln x sum_ {m = 1} ^ { infty} frac {(- 1) ^ {m} (m + 2)} {m!} left ( sum_ {j = 1} ^ {m} frac {j ^ {2} + 4j + 2} {j (j + 1) (j + 2)} يمين) × ^ {2 م} )

27. (y_ {1} = 2x ^ {3} sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m}} {4 ^ {m} m! (m + 2 )!} x ^ {2m}؛ quad y_ {2} = x ^ {- 1} left (1+ frac {1} {4} x ^ {2} right) - frac {1} { 16} left (y_ {1} ln x-2x ^ {3} sum_ {m = 1} ^ { infty} frac {(- 1) ^ {m}} {4 ^ {m} m! (م + 2)!} يسار ( sum_ {j = 1} ^ {m} frac {j + 1} {j (j + 2)} right) x ^ {2m} right) )

28. (y_ {1} = x ^ {- 1/2} sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m} prod_ {j = 1} ^ {m } (2j-1)} {8 ^ {m} m! (m + 1)!} x ^ {2m}؛ quad y_ {2} = x ^ {- 5/2} + frac {1} { 4} y_ {1} ln xx ^ {- 1/2} sum_ {m = 1} ^ { infty} frac {(- 1) ^ {m} prod_ {j = 1} ^ {m} (2j-1)} {8 ^ {m + 1} m! (m + 1)!} left ( sum_ {j = 1} ^ {m} frac {2j ^ {2} -2j-1} {j (j + 1) (2j-1)} right) x ^ {2m} )

29. (y_ {1} = x sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m}} {2 ^ {m} m!} x ^ {2m} = xe ^ {- x ^ {2} / 2}؛ quad y_ {2} = x ^ {- 1} -y_ {1} ln x + frac {x} {2} sum_ {m = 1} ^ { infty} frac {(- 1) ^ {m}} {2 ^ {m} m!} left ( sum_ {j = 1} ^ {m} frac {1} {j} right) x ^ {2 م} )

30. (y_ {1} = x ^ {2} sum_ {m = 0} ^ { infty} frac {1} {m!} x ^ {2m} = x ^ {2} e ^ {x ^ {2}}؛ quad y_ {2} = x ^ {- 2} (1-x ^ {2}) - 2y_ {1} ln x + x ^ {2} sum_ {m = 1} ^ { infty} frac {1} {m!} left ( sum_ {j = 1} ^ {m} frac {1} {j} right) x ^ {2m} )

31. (y_ {1} = 6x ^ {5/2} sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m}} {16 ^ {m} m! (m +3)!} x ^ {2m}؛ quad y_ {2} = x ^ {- 7/2} left (1+ frac {1} {32} x ^ {2} + frac {1} {1024} × ^ {4} right) - frac {1} {24576} left (y_ {1} ln x-3x ^ {5/2} sum_ {m = 1} ^ { infty} frac {(- 1) ^ {m}} {16 ^ {m} m! (m + 3)!} left ( sum_ {j = 1} ^ {m} frac {2j + 3} {j (j + 3)} right) x ^ {2m} right) )

32. (y_ {1} = 2x ^ {13/3} sum_ {m = 0} ^ { infty} frac { prod_ {j = 1} ^ {m} (3j + 1)} {9 ^ {m} m! (m + 2)!} x ^ {2m}؛ quad y_ {2} = x ^ {1/3} left (1+ frac {2} {9} x ^ {2 } right) + frac {2} {81} left (y_ {1} ln xx ^ {13/3} sum_ {m = 0} ^ { infty} frac { prod_ {j = 1 } ^ {m} (3j + 1)} {9 ^ {m} m! (m + 2)!} left ( sum_ {j = 1} ^ {m} frac {3j ^ {2} + 2j +2} {j (j + 2) (3j + 1)} right) x ^ {2m} right) )

33. (y_ {1} = x ^ {2}؛ quad y_ {2} = x ^ {- 2} (1 + 2x ^ {2}) - 2 left (y_ {1} ln x + x ^ {2} sum_ {m = 1} ^ { infty} frac {1} {m (m + 2)!} x ^ {2m} right) )

34. (y_ {1} = x ^ {2} left (1- frac {1} {2} x ^ {2} right)؛ quad y_ {2} = x ^ {- 2} يسار (1+ frac {9} {2} x ^ {2} right) - frac {27} {2} left (y_ {1} ln x + frac {7} {12} x ^ { 4} -x ^ {2} sum_ {m = 2} ^ { infty} frac { left ( frac {3} {2} right) ^ {m}} {m (m-1) ( م + 2)!} × ^ {2 م} يمين) )

35. (y_ {1} = sum_ {m = 0} ^ { infty} (- 1) ^ {m} (m + 1) x ^ {2m}؛ quad y_ {2} = x ^ { -4} )

36. (y_ {1} = x ^ {5/2} sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m}} {(m + 1) (m + 2 ) (م + 3)} x ^ {2m} ؛ quad y_ {2} = x ^ {- 7/2} (1 + x ^ {2}) ^ {2} )

37. (y_ {1} = frac {x ^ {7}} {5} sum_ {m = 0} ^ { infty} (- 1) ^ {m} (m + 5) x ^ {2m }؛ quad y_ {2} = x ^ {- 1} (1-2x ^ {2} + 3x ^ {4} -4x ^ {6}) )

38. (y_ {1} = x ^ {3} sum_ {m = 0} ^ { infty} (- 1) ^ {m} frac {m + 1} {2 ^ {m}} اليسار ( prod_ {j = 1} ^ {m} frac {2j + 1} {j + 5} right) x ^ {2m}؛ quad y_ {2} = x ^ {- 7} left (1 + frac {21} {8} x ^ {2} + frac {35} {16} x ^ {4} + frac {35} {64} x ^ {6} right) )

39. (y_ {1} = 2x ^ {4} sum_ {m = 0} ^ { infty} (- 1) ^ {m} frac { prod_ {j = 1} ^ {m} (4j +5)} {2 ^ {m} (m + 2)!} x ^ {2m}؛ quad y_ {2} = 1- frac {1} {2} x ^ {2} )

40. (y_ {1} = x ^ {3/2} sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m} prod_ {j = 1} ^ {m} (2j-1)} {2 ^ {m-1} (m + 2)!} x ^ {2m}؛ quad y_ {2} = x ^ {- 5/2} left (1+ frac { 3} {2} × ^ {2} right) )

42. (y_ {1} = x ^ {v} sum_ {m = 0} ^ { infty} frac {(- 1) ^ {m}} {4 ^ {m} m! prod_ {j = 1} ^ {m} (j + v)} x ^ {2m}؛ quad y_ {2} = x ^ {- v} sum_ {m = 0} ^ {v-1} frac {(- 1) ^ {m}} {4 ^ {m} m! prod_ {j = 1} ^ {m} (jv)} x ^ {2m} - frac {2} {4 ^ {v} v! ( v-1)!} left (y_ {1} ln x- frac {x ^ {v}} {2} sum_ {m = 1} ^ { infty} frac {(- 1) ^ { m}} {4 ^ {m} m! prod_ {j = 1} ^ {m} (j + v)} left ( sum_ {j = 1} ^ {m} frac {2j + v} { j (j + v)} right) x ^ {2m} right) )


شاهد الفيديو: 5 الغاز للاذكياء فقط, الاغبياء لن يستطيعوا حل اى منها (شهر اكتوبر 2021).